Determinants of students’ internet usage for academic purposes - Bidin, Zainol; Mohd Shamsudin, Faridahwati; Sharif, Zakiyah; Md Hashim, Mohd Farid Asraf (2011)
The aim of this study is to investigate the factors that influence students’ use of the Internet for academic purposes. This study applies underlying theory of planned behavior (TPB). Based on the theory, the original variables of attitudes, subjective norms, perceived behavioral control, and intention were hypothesized to determine Internet usage. A survey involving 422 students in various public universities in Malaysia was carried out. Results of multiple regression indicated that attitude, subjective norms, and perceived behavioral control are statistically significant in influencing intention to use the Internet for learning purposes. Meanwhile, intention was found to significantly influence Internet usage for academic purpose. Students’ intention to use the Internet for academic purposes could be predicted from their attitude, subjective norms, and perceived behavioral control at 41% level. Meanwhile, intention significantly influences Internet usage at 45% level.Implications and recommendations for practice and future work, and limitations of the study are also discussed.